Who gets a job sooner? Results from a national survey of master's graduates. Issue 1 (2nd January 2023) - Perez-Encinas, Adriana; Berbegal-Mirabent, Jasmina
ABSTRACT: This study investigates the factors that influence how long it takes for master's-level graduate students to find employment. The original contribution stems from questioning whether the structure and content of university programmes play a role in graduates' ability to secure jobs. To this end, we focus on three dimensions at three points in time after graduation: competence acquisition, teaching methods and programme characteristics. The dataset comes from a large-scale study on graduates' employability by the Observatory for University Employability and Employment (OEEU) and contains detailed information about master's degree graduates in Spain. A multinomial logit estimated by the maximum likelihood method is used to identify the critical factors influencing the likelihood of acquiring a job sooner. The findings indicate that educational programmes fail to provide the necessary competencies to ensure a smooth transition from the university to the job market and that study programme initiatives related to active learning and internships make a difference in this transition. We believe that these results shed light on specific characteristics of academic programmes and should be considered during programme design to enhance graduates' employability and faster labour market insertion.